Optical absorption and photoluminescence studies of gold nanoparticles deposited on porous silicon - Amran, Tengku Sarah Tengku (Springer, 2013)
We present an investigation on a coupled system consists of gold nanoparticles and silicon nanocrystals. Gold nanoparticles (AuNPs) embedded into porous silicon (PSi) were prepared using the electrochemical deposition method. Scanning electron microscope images and energy-dispersive X-ray results indicated that the growth of AuNPs on PSi varies with current density. X-ray diffraction analysis showed the presence of cubic gold phases with crystallite sizes around 40 to 58 nm. Size dependence on the plasmon absorption was studied from nanoparticles with various sizes. Comparison with the reference sample, PSi without AuNP deposition, showed a significant blueshift with decreasing AuNP size which was explained in terms of optical coupling between PSi and AuNPs within the pores featuring localized plasmon resonances.